Thirty years of research in family business journals: Status quo and future directions - Rovelli, Paola (2021)
Family firms are the most ubiquitous form of business organization in any world economy. Family Business Review, Journal of Family Business Strategy, and Journal of Family Business Management are the three leading academic journals exclusively dedicated to this type of firms. Since the inception of the first of the three journals in 1988, these outlets published 1381 articles dealing with family business. This study offers a comprehensive bibliometric overview of these contributions, thereby providing a complete overview of family business research conducted in the three dedicated journals in this field, and laying the ground for future developments. We do not limit our effort to describe the field from a bibliometric perspective, but furthermore unearth the most debated topics, link thematically the aspects emerging from our review, and offer promising avenues for future research.